Determination of sportsmen’s individual characteristics with the help of mathematical simulation and methods of multi-dimensional analysis - Kozina, Z.L.; Jagiello, W.; Jagiello, M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to create the most general mathematical models for determination of sportsmen’s individual motor abilities’ characteristics and individual features of qualified judo wrestlers’ fighting style. Material: in the research 22 sportsmen - judo wrestlers of average weight categories (60-81 kg) participated. Results: model, on the base of which it becomes possible to determine individual characteristics of sportsmen, has been found. With the help of factorial 4 main factors analysis of judo wrestlers’ complex fitness have been marked out. Cluster analysis of judo wrestlers’ testing indicators showed that all tested sportsmen could be divided in 3 groups (clusters). Conclusions: the received results witness about effectiveness of mathematical simulation methods, as well as methods of factorial and cluster analysis for determination of individual fighting styles of elite judo wrestlers. In their practical work coaches should apply principles of mathematical simulation for determination of individual features of fighting styles and work out methodic of judo wrestlers’ individual training.